1964
DOI: 10.1093/jaoac/47.4.645
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Residues of Cygon Insecticide and Its Oxygen Analog by Total Phosphorus Determination after Isolation by Thin-Layer Chromatography

Abstract: A total phosphorus method incorporating thin-layer chromatographic isolation is described for the determination of Cygon Insecticide (generic name, dimethoate) and its oxygen analog. Residues of the insecticides are extracted from macerated plant tissue, and the extract, after solvent partitioning and concentration, is spotted on a thin-layer chromatographic plate. After development of the plate, the areas corresponding to the two compounds are scraped and eluted. The phosphorus content of the respective eluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1966
1966
1976
1976

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Column chromatography has only been applied to malathion (440), DDT (635), and sulfoxide (755). TLC methods are now available for various pesticides (459,1015) containing phosphorus (118,176,202,235,951,1048,1067,1276,1301,1736,1969,1983,2092,2259) and chlorine (4, 69,274,950,963,1068,1192,1353,1433,2020,2064), for carbamates (290,484,528,1161), rotenone (437), and dinoseb (5). PC has been used for the same pesticides (459), including those containing phosphorus (351,352,450,867,1577,1641,2259,2305) and chlorine (87,274,564,650,…”
Section: Alkaloids Both Macekmentioning
confidence: 99%
“…Column chromatography has only been applied to malathion (440), DDT (635), and sulfoxide (755). TLC methods are now available for various pesticides (459,1015) containing phosphorus (118,176,202,235,951,1048,1067,1276,1301,1736,1969,1983,2092,2259) and chlorine (4, 69,274,950,963,1068,1192,1353,1433,2020,2064), for carbamates (290,484,528,1161), rotenone (437), and dinoseb (5). PC has been used for the same pesticides (459), including those containing phosphorus (351,352,450,867,1577,1641,2259,2305) and chlorine (87,274,564,650,…”
Section: Alkaloids Both Macekmentioning
confidence: 99%
“…Although a number of analytical methods for dimethoate residues have appeared in the literature based on such techniques as colorimetry (Chillwell and Beecham, 1960; Giang and Schechter, 1963;Van Middelem and Waites, 1964;George et al, 1966), paper chromatography (Enos and Frear, 1962), total phosphorus determination (Steller and Curry, 1964), and gas chromatography (Storherr and Watts, 1969; Steller and Pasarela, 1972; Woodham et al, 1974a,b), these methods were designed either for dimethoate alone, or for dimethoate and its oxygen analogue (dimethoxon, omethoate). In some cases, the methods require that dimethoate and dimethoxon be analyzed separately, while several of the methods quantitate without distinguishing between the two.…”
mentioning
confidence: 99%
“…4, J U L Y-A U G. However, they reported that the oxygen analog could not be satisfactorily separated from the parent material or quantitatively detected under the gas chromatographic conditions specified. Steller and Curry (5) described a total phosphorus method incorporating a thin-layer chromatographic procedure for the determination of both dimethoate and the oxygen analog.…”
mentioning
confidence: 99%